Grundtvig og Norge - Aarnes, Sigurd Aa. (Grundtvig-Studier, 1993)
Grundtvig and Norway - Some Distinctive Features By Sigurd Aa. Aamess Although this paper only examines the Norwegians’ relationship with Grundtvig, the author begins with a few remarks about Grundtvig’s relationship with Norway. Grundtvig only visited Norway once in his lifetime, but he always had special relations with Norway, inspired by the romantic interest in virgin mountain countries. Grundtvig was also a friend of the two founders of the theological faculty of the University of Christiania, and until 1815 he wanted to take up a post as a vicar in Norway. Gustav Albeck has written about Grundtvig’s relations with Norway until 1816, but unfortunately the correspondence between Grundtvig and Norwegians has not yet been published. Grundtvig’s influence in Norway is most distinctive in ecclesiastical and pedagogical fields. His hymns are abundantly represented in the Norwegian hymn book, but his .church-view. has not been accepted in Norway, although there was a Grundvigian fraction among Norwegian clergymen which seemed to be successful until the middle of the 19. century. Untill 1825 Grundtvig was considered an ally by the pietistic ‘Haugians’, but after 1850 the Norwegian pietistic theological and political administration, supported by the Faculty of Theology, fought down the Grundtvigian movement within the Church. At the same time Norway accepted the Danish folk high school idea in a version close to the Danish model. The first Norwegian folk high schools were founded in 1864 and 1867, at first supported by the poet Bjömstjeme Bjömson, with whom the Grundtvigian movement broke later, however. The Norwegian folk high schools were vey closely related to the .New Norse.-language movement and were hostil to the pietistic interpretation of Christianity. In 1875 the Norwegian Government discontinued financial support of the Grundtvigian folk high schools and established some county schools instead; they were also influenced by Grundtvigian ideas, however, and in 1908 the few survivors of the Grundtvigian schools regained their official financial support. The pietistic movement has founded a lot of non-Grundtvigian folk high schools in Norway, and although they are in opposition to Grundtvig’s ideas, they are inevitably influenced by his pedagogical views. In a paradoxical and ironical way, the author concludes, the Norwegian mixture of opposition against Grundtvigianism and acceptance of Grundtvigian hymns and pedagogical ideas illustrates the Grundtvig saying that ‘the word creates what it mentions’.